A Construção de um Gerador de Programas Aplicativos segundo Conceitos de Análise de Domínios - Fileto, Renato; Meira, Carlos Alberto Alves; Costa, Clevan Ricardo; Masshurá, Silvia Maria Fonseca Silveira (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1996.24441, 1996)
This paper is related with the experience acquired in the development of the GEMS, a source code generator intended to aid the construction of application programs, for a specific application field, from analysis and project information. The GFMS is part of a greater effort called FMS, whose goal is the development of an environment directed to the semi-automatic generation of software for agricultural activities management, through the use of domain analysis concepts and techniques. We present the basic principles employed, the general architecture of the code generator, as well as some examples and characteristics of the application programs produced by the FMS and indications of the methods to be used for the development and documentation of them. We expect that the experience described here be helpful to check the domain analysis concepts in a practical situation and to encourage and help resembling projects in other application fields.